2020
DOI: 10.1002/ejoc.202000850
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Seven Membered Oxacycles: Recent Developments and New Approaches

Abstract: This minireview focuses on recent advances in the synthesis of seven-membered ring oxacycles, whether saturated, unsaturated, fused or isolated. We cover a remarkable variety of strategies and methods developed during the past two decades, based mainly on cyclizations, ring-closing metathesis, conjugate additions, and ring expansions. The cyclizations can be generated directly or triggered through an oxocarbenium ion, carbocation or iminium-type species. Also discussed [a] Prof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Triphenylphosphine oxide coeluted with diol 15 and was carried through to the next reaction as an ∼5% impurity. R f = 0.53 (1:19 MeOH/DCM); 1 H NMR (400 MHz, MeOD): δ 5.12 (d, J = 3.9 Hz, 1H), 4 (16). Into a 500 mL round-bottom flask was dissolved 3,4:5,7-di-O-isopropylidene mannoseptanose 15 (12.0 g, 41.3 mmol, 1 equiv) in DCM (120 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Triphenylphosphine oxide coeluted with diol 15 and was carried through to the next reaction as an ∼5% impurity. R f = 0.53 (1:19 MeOH/DCM); 1 H NMR (400 MHz, MeOD): δ 5.12 (d, J = 3.9 Hz, 1H), 4 (16). Into a 500 mL round-bottom flask was dissolved 3,4:5,7-di-O-isopropylidene mannoseptanose 15 (12.0 g, 41.3 mmol, 1 equiv) in DCM (120 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…They range from completely unsaturated rings such as dibenzoxepines like janoxepine to fully saturated oxepanes such as isolaurepan. The breadth of oxepane and oxepine structures has been matched with an equally diverse set of approaches for their synthesis. Overall, these strategies can be characterized by the bond formation that closes the seven-membered ring, whether it be between carbon and oxygen (C–O) or carbon and carbon (C–C). , Seven-membered-ring carbohydrates, called septanoses, are ring-expanded homologues of natural pyranose sugars. Our group and others , develop routes for the preparation of septanosides via precursors that can participate in glycosylation reactions. Cyclic enol ethers such as 1,6-anhydro-3,4:5,7-di- O -isopropylidene-2-deoxy- d -manno-hept-1-enitol 1 (Scheme ), , or “diacetonide mannose-based oxepine”, behave in many respects like ring-expanded glycals. ,, They can be activated by epoxidation to a 1,2-anhydro sugar (i.e., 2 ) using, for example, DMDO which can be subsequently attacked by nucleophiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Mostly, transition metal-catalyzed C-C activation/functionalization through reorganization of bond connections leads to novel molecular structures with high complexity. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Recently, a review article by Sinka et al [48] reported on the recent advances in the synthesis of seven-membered ring oxacycles.…”
Section: Introductionmentioning
confidence: 99%
“…Their large molecules are hypothesized to be biosynthesized through endo -cyclization cascades of polyepoxides that break Baldwin’s rules, affording contiguously trans -fused five- to nine-membered oxacycles with many hydroxy and methyl groups. The construction of such medium-sized rings and angular methyl groups is a common problem facing the synthesis of LSPs. , In particular, syn -2,7-dimethyloxepane rings are highly distorted due to 1,3-replusion between the dimethyl groups and the ring strain of the seven-membered ring. This ring system appears in Caribbean ciguatoxin 1 (C-CTX-1), gymnocin-B, and brevisulcenal-F, all of which also have large polycyclic ether skeletons; therefore, their total syntheses are extremely challenging (Figure ).…”
Section: Introductionmentioning
confidence: 99%